Basic accounting : principles and applications - Reyes, Carlito V. (Manila : R & S Publishing, 2005)
Basic Accounting, Principles and Applications 2005 Revised Edition is a well organized and comprehensive textbook designed for use in any introductory accounting subject.
1. Introduction -- 2. The Accounting Equation -- 3. The "T" Form of the Account; Debit and Credit; Simple Financial statements -- 4. Journalizing & Posting; Preparation of a Trial Balance -- 5. Simple work Sheet; Interim Financial Statements -- 6. The Chart of Accounts; Classified Financial Statements; and the Accounting cycle -- 7. Completing the Accounting Cycle for a service business : Closing Entries; Post-Closing Trial Balance; Reversing Entries -- 9. Merchandising Operations -- 10. Completing the Accounting Cycle for merchandising: Adjusting entries; Multi column Work Sheet -- 11. Completing the accounting cycle for merchandising: Post-Closing Trial Balance; Reversing Entries -- 12. Controlling Accounts; Subsidiary Ledgers; and Special Journals.
Keywords: ACCOUNTING